ISLAMIC EDUCATION LEARNING BASED ON MULTIPLE INTELLIGENCES: INVATIVE LEARNING STRATEGIS AT CADANGPINGGAN ISLAMIC BOARDING SCHOOL - Munjiat, Siti Maryam; Firdaus, Slamet; Surahman, Aris; Sumarna, Cecep (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Bacground: Islamic Religious Education learning in the pesantren environment is often still conventional and has not been able to fully accommodate the diversity of students' potential and learning styles. This has an impact on the low active participation and learning motivation of some students. Therefore, a learning approach that is more personalized and adaptive to the needs of students is needed. Objective: this study aims to explore the implementation of multiple intelligences approach in learning Islamic Religious Education at Pondok Pesantren Cadangpinggang Cirebon. Method: using a qualitative method with a case study approach, the research involved direct observation, in-depth interviews, and analysis of learning documents over a six-month period. The results showed that the application of multiple intelligences theory in Islamic Education learning in this pesantren succeeded in significantly improving the effectiveness of the learning process and students' academic achievement. The learning model developed includes eight types of intelligences integrated into the traditional PAI curriculum, creating a learning environment that is more inclusive and adaptive to the individual needs of santri. The research findings indicate that this approach has the potential to be an alternative model in modernizing the pesantren education system without eliminating the traditional values that are the identity of pesantren. The implications of this research contribute to the development of contemporary Islamic education theory and practice that is more responsive to the diversity of learners' potential.